Human salivary pH in the occurrence of human oral protozoan parasites in Ogbeke-Nike, Enugu State, Nigeria - ADAMU, VE; Eneojo, Ndidiamaka Ijeoma; Amaechi, Augustine A.; Nwoke, Bertrand Ekejiuba Bright; Ajaero, CMU; Ukaga, Chinyere N. (Orapuh Journal, 2020)
IntroductionThe interplay between human salivary potential hydrogen (pH), which measures the acidity and alkalinity level of saliva, and the prevalence of human oral protozoan parasites should be of immense interest to clinicians who are wary of the role salivary pH plays in the regulation of the oral microbiota. Salivary pH affects the growth of microorganisms and helps maintain the oral environment.PurposeThis study was undertaken to assess the interplay between human salivary pH and infection with human oral protozoan parasites in the Ogbeke-Nike community of Enugu State, Nigeria, to enhance clinical decisions.Materials and methods The study design adopted for this research work was a cross-sectional survey. A total of 233 participants were selected, using the convenience non-probability sampling method, from 6 rural villages in the Ogbeke-Nike community, Enugu-East LGA of Enugu State, Nigeria, and were studied, using questionnaires, clinical assessments, and parasitological techniques.ResultsAnalyses of data from the study revealed that the prevalence of human oral protozoan parasites, Entamoeba gingivalis, and the mixed infections (E.gingivalis & Tichomonas tenax) were higher in participants with salivary pH of 6.0 – 6.5 (36.51%, 17.99 & and 13.23%, respectively) and zero in participants with salivary pH of 5.0 – 5.5, 8 – 8.5 and 9.0 – 9.5 (0.00% all through). T. tenax infection was more common in participants with salivary pH of 7.0 – 7.5 (16.67%). 5.29% of participants with the 6.0 – 6.5 salivary pH also manifested T. tenax, whereas the infection was not found in all other pH values. Results also indicated that there was no significant relationship between salivary pH and infection with human oral protozoan parasites (p>0.05).ConclusionsEven though there was no significant relationship between salivary pH and the occurrence of infection with human oral protozoan parasites, the peak incidence of these commensals may be positively associated with the pH value of 6.0 – 6.5. Maintaining the ideal salivary pH may be key to regulating oral microbiota.